Change in health-related quality of life among patients with a reduced ejection fraction initiating guideline-directed medical therapy. (25th November 2020) - Burch, A; Sears, S.F; Doring, M; Gummadi, S; Robertson, M; Sanchez, R; Shroff, G; Veltmann, C
Abstract: Background: Management of patients with heart failure (HF) should include patient reported outcomes (PROs). The Kansas City Cardiomyopathy Questionnaire is self-administered with subscales to evaluate HF symptom burden, physical limitations, social limitations (recreational participation), and quality of life (QoL). Change in PROs among newly diagnosed patients with HF and reduced ejection fraction (HFrEF) prescribed a wearable cardioverter defibrillator (WCD) and initiating guideline-directed medical therapy (GDMT) has not been assessed. Purpose: Examine PROs over 180 days of receiving GDMT for newly diagnosed HFrEF. Methods: Patients (n=93, 75.3% male) were enrolled ≤10 days post-hospitalization for new onset HF; all patients had an EF ≤35% and were prescribed a WCD. Health status, as measured by PRO was assessed at baseline, day 90, and day 180. Controlling for age and EF at baseline, changes in PROs over the 180-day study period were evaluated using repeated measures modeling. Pairwise comparisons with Bonferroni adjustments were used to compare adjacent timepoints. Higher scores reflect better health status. Results: After controlling for age (mean 56±13.4) and baseline EF (mean 22±7.7) improvements in health status were observed. From baseline to day 90, physical limitation, symptom frequency, QoL, and the summary score all increased (Δ: 17.8, 23.7, 28.4, 23.7, respectively; all p's <0.05). From day 90 to day 180, only QoL continued to improve (Δ 7.5, p=0.001). Change in social limitations over time was not significant (p=0.42). Conclusion: Patients report improved health status in the months following a new diagnosis of HFrEF when prescribed a WCD and GDMT. Funding Acknowledgement: Type of funding source: None